Representasi Nilai Istiqomah Dalam Film Ranah 3 Warna Karya Guntur Soeharjanto Perspektif Pendidikan Agama Islam - Sinta Dwi Prastika; Sauqi Futaqi; Mahbub Junaidi (IAIN Ambon, 2026)
Film as an audiovisual medium not only serves as mere entertainment, but can also be an educational medium that represents various values of life, including Islamic values. An important value that can be found in film is istiqomah, which is the attitude of being consistent and steadfast in doing good and facing various life challenges. The purpose of this study is to analyze how the value of istiqomah is represented in the film Ranah 3 Warna by Guntur Soeharjanto and to interpret its meaning from the perspective of Islamic Religious Education. The study uses a descriptive qualitative approach with library research as the type of research. Data is obtained through observation and documentation of the film, and then analyzed using the Miles, Huberman, and Saldana model with Stuart Hall's theory of representation as the analytical tool. From the analysis conducted, it was found that the value of istiqomah is represented through three main dimensions, namely istiqomah in pursuing ideals, istiqomah in facing life's trials, and istiqomah in maintaining a relationship with Allah SWT. This representation is shown through the dialogue, actions, and life experiences of the character Alif Fikri, which demonstrate steadfastness, patience, responsibility, as well as religiosity. This study concludes that istiqomah is a central value that underlies various positive characters in the film and is relevant as a medium for Islamic Religious Education learning, playing a role in the development of students' character.